2017
DOI: 10.1111/rego.12160
|View full text |Cite
|
Sign up to set email alerts
|

Missing links between regulatory resources and risk concerns: Evidence from the case of food safety in China

Abstract: Do resources available to regulatory agencies matter for public perceptions of social risks? In this paper we use the case of food safety in China to empirically examine the relationship between regulatory resources and risk concerns. The multilevel model estimates suggest that neither regulatory revenue nor personnel is significantly related to public concerns over food safety. There is also no significant interaction effect between regulatory resources and food scandals. Despite the fact that sufficient fisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…According to the collinear time zone diagram of keywords, the high‐frequency words in the third stage included participation, behavior, knowledge, and sustainability. The research in this period focused on the multi‐subject participation in food safety governance, consumer behavior, food safety education, and sustainable development of food safety (Chen et al., 2018; Ma & Liu, 2019; Nesbitt et al., 2014; Young et al., 2015). Investigation of consumer behavior and their level of education with regard to food safety can help government departments to better understand consumer demand for safe food.…”
Section: Resultsmentioning
confidence: 99%
“…According to the collinear time zone diagram of keywords, the high‐frequency words in the third stage included participation, behavior, knowledge, and sustainability. The research in this period focused on the multi‐subject participation in food safety governance, consumer behavior, food safety education, and sustainable development of food safety (Chen et al., 2018; Ma & Liu, 2019; Nesbitt et al., 2014; Young et al., 2015). Investigation of consumer behavior and their level of education with regard to food safety can help government departments to better understand consumer demand for safe food.…”
Section: Resultsmentioning
confidence: 99%
“…However, fiscal expenditures invested in food safety regulation may not automatically translate into government regulatory capacity, which is the crucial component of the social psychology of safety perception [ 65 ]. Resources are invested without contributing to governmental capacity building, and effective allocation matters in determining the effectiveness of the input in many complicated contexts [ 38 ]. In other words, public perceptions of food safety cannot be mitigated as long as the resources invested do not contribute to governance capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Although regulatory compliance through regulatory authorities has been well addressed in a few studies, the link between it and public perception about food safety has not been systematically examined. A recent study by Ma and Liu [ 38 ] empirically examined the effect of regulatory resources including manpower, fiscal revenue and food scandals on people’s perception about food safety risk and explored the missing linkages among them. They found that sufficient fiscal revenue and manpower do not elicit more favorable public perceptions of food safety, which could be attributed to ineffective distribution and deployment of resources.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some observed improvements, the regulatory system continues to lack sufficient capacity for its vastly expanded regulatory scope (Ma and Liu, 2017;Yee and Liu, 2020). The situation provides a unique contemporary research opportunity for investigating the capacities required for SLOs under a legal-hierarchical governance mode.…”
Section: A Collaborative Society-centered Approachmentioning
confidence: 99%